2020
DOI: 10.1097/fbp.0000000000000572
|View full text |Cite
|
Sign up to set email alerts
|

Effects of treadmill exercise and sex hormones on learning, memory and hippocampal brain-derived neurotrophic factor levels in transient congenital hypothyroid rats

Abstract: Transient thyroid function abnormalities at birth exhibit intellectual developmental and cognitive disorders in adulthood. Given the well-known effects of physical activity and sex hormones on cognitive functions and brain-derived neurotrophic factor (BDNF), the present study examined the effects of treadmill exercise, sex hormones, and the combined treatment on learning and memory and hippocampal BDNF levels in transient congenital hypothyroid rats. To induce hypothyroidism, 6-propyl-2-thiouracil was added to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
2
5
0
1
Order By: Relevance
“…In line with previous studies, we found that maternal hypothyroidism during pregnancy and lactation decreased learning and memory (Rashidy-Pour et al, 2020), as well as LTP (Derafshpour et al, 2019) in rat pups. In the current study, mothers treated with propylthiouracil (PTU) and their hypothyroid pups had significantly lower levels of thyroxine (T4) and higher levels of TSH than the corresponding control groups.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In line with previous studies, we found that maternal hypothyroidism during pregnancy and lactation decreased learning and memory (Rashidy-Pour et al, 2020), as well as LTP (Derafshpour et al, 2019) in rat pups. In the current study, mothers treated with propylthiouracil (PTU) and their hypothyroid pups had significantly lower levels of thyroxine (T4) and higher levels of TSH than the corresponding control groups.…”
Section: Discussionsupporting
confidence: 93%
“…Dams in the hypothyroid groups were administered the anti‐thyroid agent 6‐propyl‐2‐thiouracil (PTU; Sigma Co., 3050 Spruce St, St. Louis, Missouri, USA) dissolved in drinking water at a concentration of 100 ppm started on the 6th day of gestation (GD 6) and continued throughout lactation until the 21St Postnatal Day (PND 21), while the control group consumed tap water during this period (Derafshpour et al, 2019). This time frame selected for treatment was based on our recent studies, which showed the long‐term exposure of the dams to PTU, extended from early gestation to early adolescence‐induced developmental hypothyroidism in rat pups (Derafshpour et al, 2019; Rashidy‐Pour et al, 2020). The animals in choline‐treated groups received 400.0 mg/kg/day equivalent to two daily doses of 486.6 mg/kg of choline bitartrate by gavage (Derafshpour et al, 2019; Rashidy‐Pour et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The manifestation rate and morphological disorders arising in the structure of organs and tissues is determined by the degree of thyroid hormone deficiency. Most critically, hypothyroidism affects the nervous system [8], cardiovascular system (CVS) [9,10], skin [11,12], locomotor system [13] and sensory organs [3,4,14,15]. Experimental models of hypothyroidism are widely used to study morphofunctional disorders in hypothyroidism and conduct preclinical assessment of the medical-preventive activities effectiveness.…”
Section: Introductionmentioning
confidence: 99%